Research on properties of basalt fiber-reinforced asphalt mastic - Shi, Chenglin; Wang, Jianan; Sun, Shuang; Lv, Dongye; Xu, Lina; Zhang, Sufeng (Frontiers in Materials, 2023)
Basalt fiber reinforced asphalt mixture can improve engineering properties of asphalt pavement and prolong the service life of road. However, considering the composition of asphalt mixture, the study on the optimal ratio of fiber asphalt mastic, which suitable for different structural types have seldom been conducted systematically. To explore the reinforcement effect of basalt fiber on asphalt mastic, the effects of fiber content, filler-asphalt ratio and asphalt viscosity on properties of fiber asphalt mastic were investigated by orthogonal experiments. The optimal ratio of fiber asphalt mastic suitable for gap-graded and dense-graded asphalt mixture were obtained by fuzzy comprehensive evaluation (FCE) method. Meanwhile, the reinforcement effect of bundle basalt fiber (BBF), flocculated basalt fiber (FBF), polyester fiber (PF) and lignin fiber (LF) on asphalt mastic was compared and analyzed based on the optimal ratio of FBF asphalt mastic. The results showed that the optimal ratio of fiber asphalt mastic suitable for gap-graded and dense-graded asphalt mixture were that fiber content, filler-asphalt ratio and asphalt viscosity were 3%, 1.8, 1.1 Pa•s and 2%, 1.0, 0.7 Pa•s, respectively. By analyzing the properties of different types of fiber asphalt mastic, found that FBF could effectively enhance the high temperature rheological properties and low temperature tensile properties of asphalt mastic compared with other fibers. The improvement of asphalt rutting factor by FBF asphalt mastic was more than 4 times. The tensile fracture energy of fiber asphalt mastic was more than 3 times that of the corresponding asphalt. The reinforcement effect of BBF was poor, it was recommended to be broken up before using.